Perspektif Global Islam dan Pluralisme - Budhy Munawar Rachman (ILMU USHULUDDIN, 2012)
Theologically and historically, Islam can not be separated from other religions. However, the shape and style off the relationship in between them have taken place according to certain context and specific historical trajectory. Occasionally, this relationship was polemical, but more frequently it occurred in more dialogical nuance. Nevertheless, the principle of the relationship between Islam and other religions is similar, in the line of Qur'ānic teachings and as exemplified by the Prophet Muhammad in his life times, i.e. to affirm and respect other religions’ existence, and to bestow freedom that their followers could practice their faith respectively. This is as articulated by Dale F. Eickelman, a contemporary Islamicist, "The Qur'ān offers a distinctly modern perspective on the role of Islam as a force for tolerance and mutual recognition in a multiethnic, multicommunity world." This article proves that the Qur'ān accepts differences and diversities existing in human society; it even receives more specific views concerning to the plurality of believe and religious laws.